An approach to design a real-time transportation information application with enabling technologies - KuangChiu Huang; Shu-hsuan Pai (International Telecommunications Society (ITS), 2012)
Real-time transportation information (RTTI) brings convenience by immediate traffic information for drivers and minimizes uncertainty of waiting time for bus passengers. Information about heavy rains suddenly flood underground passages and traffic accidents cause road blocking can be accessed immediately through an application service via smartphones. Bus passengers can check bus waiting time from Internet before moving to bus stations by RTTI. With the development of information communication technology (ICT), benefits of real-time transportation information can be realized by an integration of location based service (LBS), smartphone, applications, 3G network and cloud computing service. In order to gain insight of RTTI service, we carry out this research with two steps. The first, the study collects existing transportation related applications from both Apple iOS platform and Google Android platform to analyze their features. Next, we analyze enabling ICT technologies to design a RTTI service model and the issue on energy saving and CO2 emission reduction. The outcome of this research can provide a clear model to assist transportation regulators, municipalities and application developers to evaluate benefits and costs of RTTI service.
Keywords: 330; real time transportation information; ICT; energy saving; CO2 emission